Ibn Kamal Pasha and his linguistic thought - Ahmed, Imad Hamid (Journal of Tikrit University for Humanities, 2024)
Allah blesses Prophet Muhammad and his follows from Al-Muhagreen and Al-Ansar and those. Who Follow the good deeds. While looking for some of the scientists resources, I came across some works for Ibn Kamal Basha Who died in 940 A.H. Which were Manu scripted and printed, I Found myself attracted to look in the fields of morphology and grammar in his work, in order to discover his unknown morphology and grammatical character of the both trend and track. And some other causes accumulated inside me to look deeply in his work, the most important of them all are:- First: - That Ibn Kamal raised a wide linguistic movement in composition and writing which were quoted in different direction of Arabic language branches like morphology, grammar, linguistic and so on. Secondly: - He is one of the most famous and biggest scientists in Al-Othmanieen reign. Thirdly: - Those who studied the Arabic language did not know much of Ibn Kamal morphological and grammatical character in comparison to the studies of studies of other language scientists and linguistic who had taken a good share of the study of the Arabic language. The study of the subject was divided into fourth chapters, precieded by an introduction and ended by conclusion